Synthesis, spectroscopic characterization, crystal structure, density functional theory studies and biological properties of coordination complex Ni(II) 2-fluorobenzoate with 3-hydroxypyridine - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT (WILEY, 2020)
A novel Ni(II) complex containing 2-fluorobenzoate and 3-hydroxypyridine ligands was synthesized and characterized using elemental analysis, Fourier transform infrared (FT-IR) spectroscopy and single-crystal X-ray diffraction. FT-IR peaks show that the carboxylate group from 2-fluorobenzoate has a monodentate coordination mode. The coordination environment around the Ni2+ ion is of distorted octahedral geometry. The octahedral geometry consists of a total of four oxygen atoms from two carboxylate groups of two fluorobenzoate anions, two water molecules and two nitrogen atoms from two 3-hydroxypyridine ligands. The complex shows excellent inhibitory effects against some metabolic enzymes. K-i values for the complex were found as 108.17 +/- 25.63, 124.88 +/- 36.20, 28.11 +/- 2.87, 20.95 +/- 5.65 and 32.63 +/- 9.67 mu M against human carbonic anhydrase I, human carbonic anhydrase II, alpha-glycosidase, acetylcholinesterase and butyrylcholinesterase, respectively. In addition, geometry optimization and vibration frequencies were calculated, and single point energy was studied based on optimization. Experimental and theoretical data were compared. The B3LYP/6-31G(d,p) basis set was used for all calculations.
Keywords: 2-fluorobenzoate; 3-hydroxypyridine; DFT calculation; metabolic enzyme inhibition; XRD; CARBONIC-ANHYDRASE; ACID; DERIVATIVES; ACETYLCHOLINESTERASE; INHIBITORS; BUTYRYLCHOLINESTERASE; L=2-HYDROXYPYRIDINE; THIOSEMICARBAZONE; FORM